Implementation of Legislative Duties for DPRD Members Bulukumba Regency 2014-2019 Period - Andi Cipta Diary Herzul; Muhammad Guntur (Jurnal Aktor, 2021)
This study aims to carry out research is to determine the implementation of the legislative duties of DPRD members of Bulukumba Regency for the 2014-2019 period. This type of research is descriptive qualitative. Data collection techniques were carried out by means of observation, interviews and documentation, while the data analysis techniques used consisted of data reduction, data presentation, and drawing conclusions or verification. The results showed that the implementation of the Legislative Duties of the Bulukumba Regency DPRD members for the 2014-2019 period included the ability of the Bulukumba Regency Regional House of Representatives to Complete the Draft of Regional Regulations Every Year Almost in Accordance with the Plan where the Ranperda was proposed based on the needs and conditions of the Bulukumba people or in other words; The ability to discuss Ranperda Ranperda that have been proposed can be completed according to a predetermined schedule as stipulated in the DPRD regulations regarding the working period of the Special Committee in discussing the draft regional regulations at all stages (Proposal, Public Examination, Presentation, Submission through Plenary Meeting, General View, Discussion on the Special Committee Level, Plenary Meeting and Determination) is completed within one year or 12 months; The implementation of the legislative function of the Regional House of Representatives of Bulukumba Regency for the 2014-2019 period is correct according to the applicable rules, from several regional regulations that have been stipulated more than 13 regional regulations which are DPRD initiative regulations, this shows that the legislative function of the Bulukumba Regency DPRD for the 2014-2019 period is still minimal where the target of the Ranperda Initiative has been set for 4-5 Ranperda each year but there are still some that are not on target. However, the DPRD has acted not only in terms of discussion and ratification, but also as the initiator of the draft regional regulation.